Fatores determinantes sobre a estrutura da metacomunidade de ostrácodes associados às macrófitas aquáticas : uma análise desconstrutiva baseada nos traços biológicos. - Campos, Ramiro de (2017)
Studies on metacommunities using the deconstruction approach based on biological traits have received a great attention in the last decade, as often describe characteristics of the species that reflect adaptations to a specific environment. However, this focus has not been addressed for the ostracods, small crustaceans highly diverse and abundant in continental aquatic environments. The objective was to investigate the influence of environmental, spatial and type of substrate factors on the metacommunity structure of periphytic ostracods in tropical floodplain lakes; and after its deconstruction according to the biological traits (size and locomotion). The analysis of variance partition was used to estimate the relative importance of each ecological factor. Ostracods, regardless of body size, are good dispersers in regional scale. As expected, swimmers ostracod were better dispersers in local scale than non-swimmers, which were influenced mainly by the architecture and complexity of aquatic macrophytes. In conclusion, the species sorting mechanism predominated on the structuring of the metacommunity of ostracods, as well as for most categories of biological traits. The analysis based on deconstruction contributed to a better understanding of processes underlying the metacommunity structure, when the metacommunity as a whole was analyzed.